Non-nutritive sweeteners: Implications for consumption in athletic populations - Machek, S. B.; Willoughby, D. S. (Strength and Conditioning Journal, 2019)
Non-nutritive sweeteners (nns) are commercially used to enhance palatability without increased sugar and/or calories in an attempt to control body weight and/or blood glucose. Recently, athletes and fitness enthusiasts are consuming more nns; however, not without concern for satiety, glucose control, and general physiological adaptations. This article aims to comprehensively evaluate the metabolic impacts of nns in cell culture, animal models, and humans, as well as establishing considerations for those seeking optimal performance and body composition. Approximately 80 articles were identified and reviewed using 29 search terms. Overall, nns consumption has the propensity to either augment or hinder exercise adaptation.